HEART RATE VARIABILITY BIOFEEDBACK AFFECTS CARDIOVASCULAR PSYCHOPHYSIOLOGY IN OLDER ADULTS. (16th November 2018) - Jester, D; Andel, R; Small, B
Abstract: Low heart rate variability (HRV) has been associated with pathological aspects of aging. Studies looking to increase HRV in older adults have relied on physical activity. We used HRV biofeedback as a behavioral neurocardiac intervention to increase global HRV and vagal tone. Twenty older adults participated in six 30-minute sessions of HRV biofeedback over three weeks. Time-domain (Standard Deviation of Normal-to-Normal intervals (SDNN), Root Mean Square of Successive Differences (RMSSD)), frequency-domain (logarithmic transformed high frequency power (LnHF)), and a nonlinear component (sample entropy (SampEn)) of HRV were measured. Covariates included age, sex, psychiatric disorders, cardiac issues, and global cognition. Growth curve models with random and fixed effects were used. Cardiac issues contributed to greater SDNN (β = 42.84, p = .02), RMSSD (β = 57.11, p = .02), and LnHF (β = 1.17, p = .04) at baseline. Controlling for covariates, values for SDNN (β = 5.20, p = .003, pseudo-R2 = 21%), RMSSD (β = 6.75, p = .008, pseudo-R2 = 23%), and LnHF (β = 0.17, p = .02, pseudo-R2 = 24%) increased over the three weeks, and SampEn (β = 0.04, p = .02) decreased. Covariates explained 26% to 36% of the variability at baseline but no variability in interindividual change. This study provides support that HRV biofeedback may increase global HRV and vagal tone in older adults. Future studies with larger samples and a control group will be needed to delineate the effect of the intervention from intraindividual differences.